Adult non-morbid and morbid obesity in Peru, 1975 - 2013 - Pajuelo Ramírez, Jaime (2019)
Introduction: Obesity is a chronic disease, which is considered as a public health problem. It affects a large number of people and requires governmental policies that encourage this situation. Objective: To determine the variations in the frequencies of non-morbid obesity (NMO) and morbid obesity (MO) according with different national surveys, and in function of socio-demographic variables. Methods: A descriptive study with data of five national surveys: Nutritional Evaluation of the Peruvian Population (ENPPE 1975), National Survey of Nutritional, Biochemical, Socio-economic and Cultural Indicators (CENAN 2005), National Household Survey (ENAHO 2009-2010) and National Household Survey (ENAHO 2012-2013). NMO was identified by a BMI of 30 to 39.99 kg/m2 and MO was defined by a BMI equal to or greater than 40 kg/m2. Results: The frequency of NMO has increased from 8,5% in 1975 to 18,5% in 2013, and the MO increased from 0,5 to 0,9% in the same period. OM is most presented in females (1,3%) with an average increasing of 0,6% (0,7% in 1975 and 1,3% in 2013) while in men it was 0,2%. Similarly, the frequency of MO was higher in the age group of 50 to 59 years, in those who live in coastal regions, urban areas and cities located below 1000 meters above sea level. Conclusions: ONM and OM, present for many years in our country, had a tendency to the progressive increase in the years of study, with a predominance of the female gender.